Exploring the impact of traditional Chinese martial arts and other martial arts on adolescent aggression: a comparative analysis of underlying mechanisms - Ting Xu; Hansen Li; Ge Rao; Feng Wang (BMC Psychology)
Abstract Background This study investigates differences in aggression among adolescents practicing traditional Chinese martial arts (MA) and other forms of MA. Additionally, it explores the underlying mechanisms, with a particular focus on the roles of self-control and depression in mediating the relationship between MA participation and aggression. Methods A total of 847 adolescent martial arts practitioners (MAP) participated in this study, including 410 traditional Chinese MA practitioners and 437 practitioners of other MA (e.g., Taekwondo, kickboxing). The sample comprised 427 males, with a mean age of 13.45 years (SD = 1.07). Participants completed the Physical Activity Rating Scale, Self-Control Scale, Depression Scale, and Aggression Scale. Data were analyzed using IBM SPSS Statistics 21.0 and Process 4.0, with significance levels set at p < 0.05. Results (1) No significant differences in aggression were observed between adolescents practicing traditional Chinese MA and those practicing other MA. (2) MA exercise level negatively predicted aggression (β = -0.126, p < 0.001). (3) A chain mediation analysis indicated two pathways through which MA exercise level was associated with aggression: (a) MA exercise level → self-control → aggression, accounting for 68.25% of the total effect, and (b) MA exercise level → self-control → depression → aggression, accounting for 20.63%. Conclusions Regular participation in MA is a potential strategy for reducing aggression and psychological distress while enhancing self-control. Educators and MA organizations should emphasize both technical training and ethical instruction to foster self-regulation and emotional well-being in adolescents. Moreover, increasing MA training intensity may further amplify these benefits.